Fisuras en la cotidianidad. Sobre La encomienda de Margarita García Robayo y Flores en la basura de Violeta Serrano - Katarzyna Gutkowska-Ociepa (Studia Romanica Posnaniensia, 2024)
The cross-interpretation of two texts: a novel by Margarita García Robayo, The Delivery (2022), and an essay by Violeta Serrano, “Flowers in the Dustbin” (2022) focuses on four main issues: the intention that reveals itself in the genre, the considerations on everyday life in regard to the family baggage that one carries and has to deal with in order to redefine their own identity, the migrant’s status and its relation to the quotidian dimension of being, and, lastly, the employment precariousness and financial difficulties common in the lives of the millennials. The article also outlines the significance of Argentina as setting in both texts. The methodological frame is constituted by the metatextual ponderings by García Robayo, the notion of Everyday according to Alfred Schutz, Maurice Blanchot and Roland Barthes, as well as a concept of degrowth by Serge Latouche.